2021
DOI: 10.1016/j.sjbs.2020.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of inland sand dunes “nafuds” as a hyper-arid habitat, Saudi Arabia: Floristic and plant associations diversity

Abstract: Sand seas of Saudi Arabia cover about one-third of the Arabian Peninsula and are still poorly explored in scientific literature. This study aimed to address the floristic structure and association diversity of the inland sand seas in central Saudi Arabia after 20 years of protection. Twenty-three relevés were selected in Nafud Al-Urayq reserve to cover different sandy dune variations. These relevés are subjected to floristic and multivariate analysis of classification with TWINSPAN and ordination with DECORANA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Arid and semiarid regions in Saudi Arabia harbours diversity of annual and perennial plant species due to unique combinations of habitats and ecosystems [1][2][3][40][41][42][43]. In this study, 163 species belong to 124 genera, and 41 families were reported from the 5 sites in Tabuk region.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Arid and semiarid regions in Saudi Arabia harbours diversity of annual and perennial plant species due to unique combinations of habitats and ecosystems [1][2][3][40][41][42][43]. In this study, 163 species belong to 124 genera, and 41 families were reported from the 5 sites in Tabuk region.…”
Section: Discussionmentioning
confidence: 92%
“…This number of species is higher compared with the earlier study conducted by Al-Mutairi et al [42], who reported a total of 96 species. However, 135 plant species were reported in the hyper-arid environment of "nafuds" sand dunes in the middle of Saudi Arabia [43]. In desert-wetland, Galal et al [3] reported 142 species in Taif, southwestern region of Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…grazing while public areas have less number of herbs and grasses [57,58]. Protected site of Derawar region of Cholistan Desert have dominant families i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Kingdom of Saudi Arabia (KSA) is known for its many habitats and climatic regimes, including valleys, mountains, rocky deserts, sand dunes, plateaus, plains, and salt pans (El-Sheikh et al 2021). There are approximately 2,290 species of plants in the KSA, of which 9 are Gymnosperms and 27 are Pteridophytes.…”
Section: Introductionmentioning
confidence: 99%